Unimas, Utsunomiya University carry out e-EduTour2021 - Soubakeavathi, Rethinasamy; Gabriel, Lihan; Dayang Hartijah, Abang Ahmad; Damien, Mikeng; Nurul Huzaimah, Hussien; Liyana, Rosli; Keezrawati, Mujan Yusuf; Joseph, Ramanair (New Sarawak Tribune, 2021)
KUCHING: Universiti Malaysia Sarawak (Unimas) and its strategic partner Utsunomiya University Japan (UU) have carried out their student mobility programme virtually.